Can drifting objects drive the movements of a vulnerable pelagic shark?. Issue 1 (19th August 2020) - Bonnin, Lucas; Lett, Christophe; Dagorn, Laurent; Filmalter, John David; Forget, Fabien; Verley, Philippe; Capello, Manuela
Abstract: Juvenile silky sharks ( Carcharhinus falciformis) regularly associate with floating objects yet the reasons driving this behaviour remain uncertain. Understanding the proportion of time that silky sharks spend associated with floating objects is essential for assessing the impacts of the extensive use of fish aggregating devices (FADs) in the tropical tuna purse‐seine fisheries, including increased probability of incidental capture and the potential of an ecological trap. Previous studies provided insight into the amount of time that silky sharks spent at an individual FAD but were unable to assess neither the time spent between two associations nor the proportion of time spent associated/unassociated. The percentage of time that juvenile silky sharks spend unassociated with floating objects was estimated through the analysis of horizontal movements of 26 silky sharks monitored with pop‐up archival tags. Under the assumption that a high association rate with drifting FADs would align the trajectories of tracked sharks with ocean surface currents, a novel methodology is proposed, based on the comparison of shark trajectories with simulated trajectories of passively drifting particles derived using a Lagrangian model. Results revealed that silky shark trajectories were divergent from surface currents, and thus unassociated with FADs, for at least 30% of their time. The potential of the methodology and the results are discussed in the context of increasing FAD densities in the Indian Ocean.